Internet-based Interacting Together Everyday, Recovery After Childhood TBI (I-InTERACT): Protocol for a multi-site randomized controlled trial of an internet-based parenting intervention. (July 2017) - Narad, Megan E; Taylor, H Gerry; Yeates, Keith O; Stancin, Terry; Kirkwood, Michael W; Wade, Shari L
Objectives: We discuss the rationale and description of the Internet-Based Interacting Together Everyday, Recovery After Childhood TBI (I-InTERACT), a telehealth intervention designed to promote positive parenting skills through live in-session skills practice and coaching. A second objective is to describe the protocol of a three-armed (Internet Resource Comparison, I-InTERACT, and I-InTERACT Express) multi-site randomized controlled trial (RCT) designed to examine intervention effectiveness. Method: Participants included parents of children ages 3–9 who sustained a moderate or severe traumatic brain injury (TBI) any time since birth. Measures assessing parenting behaviors, parent–child interaction, parent/family factors, and child factors were collected prior to intervention, 3 months after enrollment and 6-months after enrollment. Results: This protocol manuscript was submitted before the completion of data collection and prior to any data analysis. It is expected that the I-InTERACT and I-InTERACT Express interventions will be associated with an increase in positive parenting behaviors, and a decrease in negative parenting behaviors, parental distress, and child behavior problems. Finally it is expected that socioeconomic status, life stressors, and social resources will moderate treatment effects. Conclusions: The study described in this protocol paper represents one of the first large multi-site RCTs of a parenting intervention designed to promote positive parenting skills in families with young children who sustained a TBI. We plan to disseminate findings to patients and families as well as clinical and research professionals, and begin to develop a research base for this telehealth intervention.